2016
DOI: 10.1021/jacs.6b05025
|View full text |Cite
|
Sign up to set email alerts
|

A pH-Induced Switch in Human Glucagon-like Peptide-1 Aggregation Kinetics

Abstract: Aggregation and amyloid fibril formation of peptides and proteins is a widespread phenomenon. It has serious implications in a range of areas from biotechnological and pharmaceutical applications to medical disorders. The aim of this study was to develop a better understanding of the mechanism of aggregation and amyloid fibrillation of an important pharmaceutical, human glucagon-like peptide-1 (GLP-1). GLP-1 is a 31-residue hormone peptide that plays an important role regulating blood glucose levels, analogues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
61
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(69 citation statements)
references
References 25 publications
7
61
1
Order By: Relevance
“…We showed that above a certain threshold, the lag phase of Aβ fibrillization by ThT increases, and this delay of fibril formation was confirmed by solution NMR. These findings are consistent with the results of Jackson and coworkers, who have recently demonstrated the presence of pH‐sensitive oligomers, which compete with fibril formation during aggregation of glucagon‐like peptide . The high concentration assemblies of Aβ40 were more compact than the corresponding monomer as measured by SAXS and were determined to consist primarily of dimers by AUC.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We showed that above a certain threshold, the lag phase of Aβ fibrillization by ThT increases, and this delay of fibril formation was confirmed by solution NMR. These findings are consistent with the results of Jackson and coworkers, who have recently demonstrated the presence of pH‐sensitive oligomers, which compete with fibril formation during aggregation of glucagon‐like peptide . The high concentration assemblies of Aβ40 were more compact than the corresponding monomer as measured by SAXS and were determined to consist primarily of dimers by AUC.…”
Section: Discussionsupporting
confidence: 91%
“…However, mathematical modeling of amyloid formation has suggested that as the concentration exceeds a threshold, the energetic forces favor oligomerization rather than fibrillization . This phenomenon has been observed experimentally for a number of fibril‐forming peptides and proteins . Knowing the structural contacts of such an oligomer could help prevent the on‐pathway oligomer structures that may be associated with toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…At pH . 8.0, GLP-1 follows the more common nucleation-polymerization kinetics with t 1/2 and t lag decreasing with increasing peptide concentration (figure 5b-d); however, at pH 7.5, the kinetics reverse such that both lag time and t 1/2 decrease with increasing peptide concentration indicating offpathway oligomers have formed [1]. At an intermediate pH, 8.0, there is little dependence on peptide concentration as there is a delicate balance between on-and off-pathway species [1].…”
Section: Peptide Concentrationmentioning
confidence: 95%
“…8.0, GLP-1 follows the more common nucleation-polymerization kinetics with t 1/2 and t lag decreasing with increasing peptide concentration (figure 5b-d); however, at pH 7.5, the kinetics reverse such that both lag time and t 1/2 decrease with increasing peptide concentration indicating offpathway oligomers have formed [1]. At an intermediate pH, 8.0, there is little dependence on peptide concentration as there is a delicate balance between on-and off-pathway species [1]. Although off-pathway oligomers have been observed now for a number of peptides and proteins [1,73,74] these systems have not been studied in the detail that peptides and proteins showing simpler nucleation-polymerization kinetics have been and therefore not much is known about the nature of off-pathway oligomers, for example, their size, structure and cellular toxicity.…”
Section: Peptide Concentrationmentioning
confidence: 95%
See 1 more Smart Citation